2009
DOI: 10.3109/08860220903216113
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and Serum Biomarkers after Cardiac Catheterization in Diabetic Patients with Stable Angina and without Severe Chronic Kidney Disease

Abstract: Background/Aims. Different serum and urinary biomarkers have been recently proposed to serve as markers of acute kidney injury. We tested the hypothesis whether NGAL and other biomarkers could represent an early biomarker of contrast nephropathy (CIN) in diabetic patients with normal serum creatinine undergoing cardiac catheterization in comparison with nondiabetic patients. Methods. Serum, urinary NGAL, cystatin C, urinary kidney injury molecule-1 (KIM-1), interleukin-18 (IL-18), and liver-type fatty acid bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 37 publications
5
59
1
1
Order By: Relevance
“…Studies including NGAL and cystatin C have suggested that NGAL had a better performance in identifying acute kidney dysfunction than cystatin C (29,30). In our patients, although those developing type 1 cardiorenal syndrome had higher levels of NGAL and cystatin C than the others, the performance of cystatin C was nonsatisfactory as expressed by an AUC of 0.68.…”
Section: Discussioncontrasting
confidence: 53%
“…Studies including NGAL and cystatin C have suggested that NGAL had a better performance in identifying acute kidney dysfunction than cystatin C (29,30). In our patients, although those developing type 1 cardiorenal syndrome had higher levels of NGAL and cystatin C than the others, the performance of cystatin C was nonsatisfactory as expressed by an AUC of 0.68.…”
Section: Discussioncontrasting
confidence: 53%
“…Eight of them were diabetic (8 out of total 31 diabetic patients). This agreed with Malyszako et al 15 who concluded that diabetic patients are more vulnerable and prone to develop contrast nephropathy. Toprak reported that the most important and well established patient-related risk factors for CIN are CKD particularly CKD combined with diabetes mellitus and advanced age.…”
Section: Discussionsupporting
confidence: 90%
“…Conflicting results, regarding the time course of L-FABP, were obtained by Malyszko et al, (2009) [32]; who performed a study on 140 patients (i.e., 70 type 2 diabetic patients in comparison to 70 nondiabetic patients) with normal serum creatinine undergoing cardiac catheterization; they evaluated Serum, urinary NGAL, cystatin C, urinary KIM-1, IL-18, and L-FABP before and 2, 4, 8, 24, and 48 hours after cardiac catheterization, and observed a significant rise in L-FABP 24 and 48 hours after PCI in both groups without any significant changes 2-8 hours after the procedure (in diabetics: baseline=6.39 (0.96-7.21) pg/ml, 8h value=10.43 (2.31-51.33) pg/ml, 24h value=18.92 (5.43-112.12) pg/ml; in non-diabetics: baseline=5.32 (0.64-5.43) pg/ml, 8h value=6.38 (0.88-22.27) pg/ml, 24h value=16.01 (4.17-98.45) pg/ml); on the other hand, Serum cystatin C increased significantly after 8 hours, reaching its peak 24 hours after cardiac catheterization in both groups. In patients with CIN, Cystatin C was higher only 8 and 24 hours after cardiac catheterization, whereas L-FABP was significantly higher only 24 hours after the procedure.…”
Section: -Fasting Plasma Glucose Level By Colorimetric Methodsmentioning
confidence: 93%